Introducing a New Approach combining Communicative Capabilities and Social Software for an Optimized Handling and Improved Transparency of Virtual, International Projects - Benjamin Thienel (Journal of Applied Leadership and Management, 2016)
Is the overall project handling of virtual, international projects correlated with specific communicative capabilities of the project leader supported by selected elements of Social Software? Is the overall project transparency of virtual, international projects correlated with the usage of specific elements of Social Software?
Keywords: 650; virtual project; international project; improved transparency; new approach; communicative capability; social software